(untitled) (Quinto Sol, 2014)
In the present paper we analyze the emergence of political-union identities, and its search for new forms of organization, in the final period of the dictatorship called “Revolución Argentina”. To do so we reconstruct the different strategies of the new peronist unionism, from 1970 until 1973, by portraying their relations with previous combative experiences, and their opposition to the national CGT led by Rucci, to the dictatorship and to Lanusse’s political exit. The empirical work will be analyzed in the frame of the question about the relationship between institutions and political identities, specifically the organizations (unions and unions groupings) with the workers and popular identities, and the dispute over their representation.